Penguatan Pendidikan Karakter Disiplin dan Peduli Sosial pada Pembelajaran Tematik Kelas I di Sekolah Dasar Negeri 03 Kota Pagaralam - Aquami Aquami; Mardiah Astuti; Sunardi Sunardi (JIP Jurnal Ilmiah PGMI, 2020)
This study aims to describe and analyze the strengthening of disciplinary character education and social care in Thematic Learning at 03 State Elementary Schools in Pagaralam City. This research includes planning carried out by teachers in strengthening the character of discipline and social care in thematic learning in grade I, and implementing thematic learning in strengthening. Discipline character and social care for grade I (one) students. The research approach is qualitative with the type of case study research. The results showed that the learning planning process of disciplinary character and social care is contained in the syllabus and the Learning Implementation Plan (RPP) and the implementation of Thematic Learning uses the Scientific approach, Problem Based Learning learning models, and the methods used in strengthening character are reward and punishment and peer tutors.